2019
DOI: 10.1080/0020739x.2019.1657596
|View full text |Cite
|
Sign up to set email alerts
|

The potential of recreational mathematics to support the development of mathematical learning

Abstract: This provides an opportunity for fun and play, while developing graduate skills. It teaches some combinatorics, graph theory, game theory and algorithms/complexity, as well as scaffolding a Pólya-style problem-solving process. The assessment of problem-solving as a process via examination is outlined. Student feedback gives some indication that students appreciate the aims of the module, benefit from the explicit focus on problem-solving and understand the active nature of the learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…However, recreational mathematical items were low in frequency in comparison with those in other countries, such as Russia, a traditional mathematics power, where many interesting items are couched in the setting of a game rich in recreational mathematics [82] (p. 249), which is quite different from Chinese test items. Some studies have shown that recreational mathematics can promote students' mathematical skills, learning achievement, and learning motivation [83,84]. In the future, test designers in China could try to design more test items with interesting contexts.…”
Section: Discussionmentioning
confidence: 99%
“…However, recreational mathematical items were low in frequency in comparison with those in other countries, such as Russia, a traditional mathematics power, where many interesting items are couched in the setting of a game rich in recreational mathematics [82] (p. 249), which is quite different from Chinese test items. Some studies have shown that recreational mathematics can promote students' mathematical skills, learning achievement, and learning motivation [83,84]. In the future, test designers in China could try to design more test items with interesting contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Mathematical thinking skills and styles are both involved in writing proofs of mathematical statements. The article written by Rowlett et al (2019) is related to the need for thinking or mathematical skills in learning that can be used effectively to motivate student engagement by developing an understanding of mathematical ideas or concepts. The article written based on the results of a study by Huang & Lin (2013) shows that the holistic and analytical thinking styles presented in teaching materials and teaching activities can have an impact on students' understanding of mathematical concepts.…”
Section: Title Abbreviation Author (S) and Year Sourcementioning
confidence: 99%
“…Finally, referring to articles discussing mathematical thinking styles (study from : Haavold, 2021;Huang & Lin, 2013;Rowlett et al, 2019;Schütte et al, 2021;Spangenberg, 2012), can contribute to a wealth of literature for the subsequent studies, and it is very clear that the differences in students' thinking styles become a major challenge to the teacher's pedagogical practice in teaching mathematics. Likewise, findings that discuss mathematical thinking styles in science learning (for example, studies by O 'Boyle, 2008;Utami et al, 2021;Vasileva-Stojanovska et al, 2014), their findings imply that instructional techniques should be developed by utilizing tendency of mathematics learning style which can be a reference for science learning.…”
Section: Constructionist Co-designmentioning
confidence: 99%
“…Murtaqi;; Soeviatulfitri & Kashardi, (2020) in their research also argue that there is an effect of applying the Osborn learning model on improving students' mathematical critical and creative thinking skills. Meanwhile, according to (Rowlett et al, 2019), there is an effect on students' mathematical problem-solving ability by applying the learning model with the Osborn method with mnemoic techniques through the theory of constructivism. The Osborn learning model is effectively used in mathematics learning to improve student learning outcomes (Lanya & Aini, 2019;Murtaqi;.…”
Section: Introductionmentioning
confidence: 99%